Dr. Edmar Minchio — Deep Plane Facelift — Rio de Janeiro - Minchio, Edmar (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Edmar Minchio, practicing in Rio de Janeiro, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003351; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; rio de janeiro